Increasing the wear resistance of steel bandage by surface laser modification with tungsten carbide particles - Aleksander G. Grigor’Yants; Igor’ N. Shiganov; Roman S. Tret’Yakov; Aleksander I. Misyurov; Roman D. Asyutin; Aleksey A. Drenin; Aleksander V. Perestoronin (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
Currently, the wheel flange limiting wear is the main reason of the railroad wheels trueing. In order to enhance the wear resistance of the wheels to the required level, composition of their surface shall be changed, which is proposed to do by the method of laser surface modification introducing spherical particles of tungsten monocarbide with diameter from 50 to 150 μm. It was found out that introduction of the said particles into steel, which composition corresponds to grade 2 as per GOST 398-2010, results in reduction of microhardness of matrix metal formed on the composite layer surface as long as the content of tungsten monocarbide particles is increased. This phenomenon shall be probably connected with the change of chemical composition and stress-strain state of metal. Examination of wear resistance using roller samples demonstrated that growth of the volumetric fraction of reinforcing particles significantly increases the wear resistance. Laser heat processing of the surface without introducing the particles results in the wear resistance increase too. Wear and tear of the counter rollers cut from the rail operated in pair with the reinforced rollers cut from the tread band is less than in the pair with untreated rollers. Introduction of reinforcing particles is much more important than matrix hardening for increasing the wear resistance. It is demonstrated that cross-crack defects can be formed in modified layers, which quantity depends on the volumetric fraction of reinforcing particles. When content of tungsten monocarbide is less than 10%, cracks are not observed. According to the totality of properties, the best content of reinforcing particles shall amount from 8 to 10% of the volume.